Choledochal Cyst with Chronic Pancreatitis: Presentation and Management - Saluja, Sundeep Singh; Mishra, Pramod Kumar; Nayeem, Mohammed; Nag, Hridya Hulas (JOP. Journal of the Pancreas, 2010)
Context Choledochal cysts are benign congenital cystic dilatations of the common bile duct. They are usually associated with pancreatobiliary malunion resulting in long-term complications, such as acute pancreatitis and bile duct cancer. However, the occurrence of chronic pancreatitis with a choledochal cyst is rarely reported. Case reports We report three cases of choledochal cysts associated with chronic pancreatitis with their presentation and management. The choledochal cysts were classified according to the Alonso-Lej classification with Todani modifications, based on radiographic and operative findings. Chronic pancreatitis was defined using Marseille criteria (1984). Two patients had a type I choledochal cyst and one had a type IV-A. All cases had chronic calcific pancreatitis with a grossly dilated main pancreatic duct. Abdominal pain was the most common presentation, present in all three patients while jaundice was seen in one patient. The laboratory parameters and MRI/MRCP helped to confirm the diagnosis. All patients underwent cyst excision with drainage and had an uneventful postoperative course. At a median follow-up of 9 months, two patients were asymptomatic and one patient, who developed duodenal obstruction, underwent gastrojejunostomy. Conclusions the association of a choledochal cyst with chronic pancreatitis may be etiologically related. Excision of the cyst with lateral pancreaticojejunostomy can be performed safely and is usually curative. Image: MRCP showing a type I choledochal cyst.